2018
DOI: 10.1007/s12035-018-0895-1
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Sulfasalazine and Valproic Acid Promotes Human Glioblastoma Cell Death Through Imbalance of the Intracellular Oxidative Response

Abstract: Glioblastoma (GBM) is the most common and aggressive malignant primary brain tumor and still lacks effective therapeutic strategies. It has already been shown that old drugs like sulfasalazine (SAS) and valproic acid (VPA) present antitumoral activities in glioma cell lines. SAS has also been associated with a decrease of intracellular glutathione (GSH) levels through a potent inhibition of xc- glutamate/cystine exchanger leading to an antioxidant deprotection. In the same way, VPA was recently identified as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…With a very poor survival of 14–16 months in newly diagnosed patients, GBM accounts for more than 50% of malignant gliomas [1] , [2] , [3] . Surgical resection of tumors with accompanying or concurrent radiation or chemotherapy, either alone or in combination, has not been an entirely successful curative approach for treating GBM.…”
Section: Introductionmentioning
confidence: 99%
“…With a very poor survival of 14–16 months in newly diagnosed patients, GBM accounts for more than 50% of malignant gliomas [1] , [2] , [3] . Surgical resection of tumors with accompanying or concurrent radiation or chemotherapy, either alone or in combination, has not been an entirely successful curative approach for treating GBM.…”
Section: Introductionmentioning
confidence: 99%
“…Barneh's research shown that valproic acid inhibits stromal cell function and exerts anticancer effects [57]. In GBM, valproic acid is considered a favourable SR drug that acts through multiple mechanisms [58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…It is done by an increasing production of reactive oxygen species, p21 expression, G2/M cell cycle arrest, suppressing the repair of DNA double strand break, and activating pro-apoptotic signaling [25,26,27,28]. It was shown that NaVP alone and in combination with other chemotherapeutic drugs has an antiangiogenetic and antiproliferative effect on GBM cells and on in vivo rodent glioma tumors [29,30,31]. In line with these studies, we observed an antiproliferative effect on GBM cells by NaVP treatment (Figure 6), without, however, significant effects on cell viability under our experimental conditions (Figure 5).…”
Section: Discussionmentioning
confidence: 99%